a - Bunyard, Peter; Unillanos
In the debate about global warming we forget at our peril the role of ecosystems in giving us a climate we can live with. Life co-evolving with our planet over thousands of millions of years has created an enviroment apt for millions upon millions of species.
Keywords: CLIMA - COLOMBIA - PUBLICACIONES SERIADAS; CLIMA TROPICAL - PUBLICACIONES SERIADAS